Gas diffusion layer, its manufacturing method, and polymer electrolyte fuel cell
The gas diffusion layer with a porous substrate and microporous layer, optimized for crack density and concave area ratio, addresses liquid water drainage issues in solid polymer fuel cells, enhancing power generation efficiency by preventing flooding and maintaining oxygen transport.
Patent Information
- Application Number
- JP2021104932
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-24
- Publication Date
- 2025-02-03
- Estimated Expiration
- 2041-06-24
AI Technical Summary
Conventional methods for improving liquid water drainage in solid polymer fuel cells are insufficient, leading to reduced performance due to excessive liquid water accumulation, which inhibits oxygen transport and reduces power generation efficiency.
A gas diffusion layer with a porous substrate and a microporous layer having specific crack density, crack width, and area ratio of concave parts, optimized through controlled manufacturing conditions, enhances water drainage by forming optimal gaps between the cathode side catalyst layer and the microporous layer.
The optimized gas diffusion layer achieves high cold voltage performance by effectively draining water, preventing flooding and maintaining oxygen transport, thereby improving the fuel cell's power generation efficiency.
Smart Images

Figure 0007625355000002 
Figure 0007625355000003 
Figure 0007625355000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a gas diffusion layer and a manufacturing method thereof, and a polymer electrolyte fuel cell, and more particularly to a gas diffusion layer having high liquid water discharge performance and a manufacturing method thereof, and a polymer electrolyte fuel cell including such a gas diffusion layer. [Background technology]
[0002] A polymer electrolyte fuel cell includes a membrane electrode assembly (MEA) in which electrodes (catalyst layers) are bonded to both sides of an electrolyte membrane made of a solid polymer electrolyte. In a polymer electrolyte fuel cell, a gas diffusion layer is generally disposed on the outside of the catalyst layer. The gas diffusion layer is for supplying reactant gas and electrons to the catalyst layer, and is made of carbon paper, carbon cloth, or the like. Furthermore, a separator having a gas flow path is disposed on the outside of the gas diffusion layer. A polymer electrolyte fuel cell usually includes a structure (fuel cell stack) in which a plurality of unit cells each consisting of such an MEA, gas diffusion layer, and separator are stacked.
[0003] In solid polymer fuel cells, the electrolyte membrane needs to have an appropriate water content to exhibit good proton conductivity. Therefore, if the temperature of the fuel cell during power generation is high or the water content in the supply gas is low, the electrolyte membrane dries out and performance decreases. On the other hand, when power is generated using a polymer electrolyte fuel cell, water is produced on the cathode side due to an electrode reaction. Therefore, when the temperature of the fuel cell is low and the water content in the supply gas is high, liquid water is likely to be produced in the gas diffusion layer on the cathode side. Excess liquid water inhibits oxygen transport and causes a decrease in the performance of the fuel cell.
[0004] In order to solve this problem, various proposals have been made in the past. For example, Patent Document 1 discloses a fuel cell in which holes are provided in the cathode-side diffusion layer, and a porous water-guiding member for promoting the discharge of water is inserted into the holes. This document describes that when a water-guiding member is inserted into a hole provided in the cathode diffusion layer, the water remaining in the cathode diffusion layer passes through the water-guiding member, and the discharge of the water is promoted.
[0005] Patent Document 2 discloses a polymer electrolyte fuel cell in which a through hole having a diameter of more than 1 mm is provided in the cathode side gas diffusion layer. The same document states: (A) When starting up at temperatures below freezing, frost forms at the interface between the catalyst layer and the diffusion layer, impairing the start-up capability of the fuel cell. (B) When through holes are provided in the cathode-side gas diffusion layer, freezing occurs mainly on the inner periphery of the through holes, and freezing at the interface between the catalyst layer and the diffusion layer is reduced; and (C) This improves starting performance when starting at temperatures below freezing. is stated.
[0006] Furthermore, Patent Document 3 states: (a) applying an ink for forming an intermediate layer (water-repellent layer) containing carbon fibers to the surface of the water-repellent treated carbon paper so that the carbon fibers are arranged parallel to each other, and then drying and baking the ink; (b) Using a pinholder, a first vertical hole is formed through the intermediate layer and the carbon paper. The gas diffusion layer obtained by the above process is disclosed. The same document states: (A) The water in the gas diffusion layer cannot be sufficiently discharged by the vertical hole alone, and (B) When carbon fibers are arranged in parallel in the intermediate layer and first vertical holes are formed penetrating the gas diffusion layer, gaps (passages through which water can pass) are formed between the carbon fibers, and the gaps communicate with the first vertical holes, facilitating the discharge of water. is stated.
[0007] Patent Documents 1 to 3 propose methods for improving the drainage performance of liquid water on the cathode side. However, the drainage performance of the conventional methods is insufficient. For example, the method of Patent Document 1 has insufficient drainage performance because the number density of the drainage holes is low. Furthermore, in the method of Patent Document 2, the diameter of the through-holes is too large, so that liquid water accumulates in the through-holes under high current density conditions, hindering the supply of gas to the catalyst layer. Furthermore, in the method of Patent Document 3, since the carbon fiber does not have micropores through which gas can pass, even if there are through holes (first vertical holes), when liquid water is generated and water accumulates in the intermediate layer, gas diffusibility decreases significantly. Therefore, the conventional method cannot suppress the decrease in power generation performance (cold voltage) in an environment where liquid water is likely to be generated. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2008-034301 A [Patent Document 2] JP 2011-249193 A [Patent Document 3] JP 2008-277126 A Summary of the Invention [Problem to be solved by the invention]
[0009] An object of the present invention is to provide a gas diffusion layer having high liquid water discharge performance and a method for producing the same. Another object of the present invention is to provide a polymer electrolyte fuel cell equipped with such a gas diffusion layer. [Means for solving the problem]
[0010] In order to solve the above problems, the gas diffusion layer according to the present invention comprises: A porous substrate made of a conductive material; A microporous layer formed on the surface of the substrate; Equipped with The microporous layer is The crack density is 2 / mm 2 More than 11 pieces / mm 2 is as follows: The area ratio of the recesses is 11% or more and 15% or less.
[0011] The polymer electrolyte fuel cell according to the present invention has the following configuration. (1) The solid polymer fuel cell is a membrane electrode assembly in which a cathode catalyst layer and an anode catalyst layer are bonded to both sides of an electrolyte membrane made of a solid polymer electrolyte membrane; a cathode-side gas diffusion layer disposed on the outer side of the cathode-side catalyst layer; an anode-side gas diffusion layer disposed on the outer side of the anode-side catalyst layer; a cathode-side separator disposed on the outer side of the cathode-side gas diffusion layer; an anode-side separator disposed on the outer side of the anode-side gas diffusion layer; It is equipped with: (2) The cathode side gas diffusion layer is made of the gas diffusion layer according to the present invention.
[0012] The method for producing a gas diffusion layer according to the present invention comprises the steps of: A first step of preparing a porous substrate made of a conductive material; a second step of mixing the conductive particles, the water-repellent resin, the dispersant, the thickener, and water to prepare a slurry; A third step of applying the slurry to a surface of the substrate and drying the slurry; A fourth step of calcining the substrate to obtain the gas diffusion layer according to the present invention. It is equipped with: Effect of the Invention
[0013] When a microporous layer is formed on the surface of a porous substrate, optimizing the manufacturing conditions makes it possible to obtain a gas diffusion layer in which the number density of cracks and the area ratio of recesses are within a predetermined range. Next, in the case of producing a polymer electrolyte fuel cell using such a gas diffusion layer, by optimizing the production conditions, it is possible to form appropriate voids at the interface between the cathode side catalyst layer and the microporous layer. Both the cracks in the microporous layer and the gaps at the cathode catalyst layer / microporous layer interface affect the drainage performance on the cathode side. Therefore, optimizing the manufacturing conditions to optimize these factors leads to a polymer electrolyte fuel cell that exhibits a high cold voltage. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is a schematic diagram of an X-ray CT measuring tool. [Diagram 2] Figure 2(A) is an example of an X-ray CT image of a longitudinal section of a gas diffusion layer (GDL) and catalyst coated membrane (CCM) laminate. Figure 2(B) is an in-plane cross-sectional image (including gaps) of the microporous layer (MPL) / catalyst layer (CL) interface extracted from the X-ray CT image. Figure 2(C) is an in-plane cross-sectional image (including cracks) of the microporous layer (MPL) / catalyst layer (CL) interface extracted from the X-ray CT image.
[0015] [Diagram 3] Figure 3(A) is an example of an in-plane cross-sectional image of the microporous layer (MPL) / catalyst layer (CL) interface extracted from an X-ray CT image. Figure 3(B) is a schematic diagram of a gap included in the in-plane cross-sectional image. Figure 3(C) is a schematic diagram of a crack included in the in-plane cross-sectional image. [Figure 4] FIG. 13 is a diagram showing the relationship between the number density of cracks and cold voltage. [Diagram 5] FIG. 13 is a diagram showing the relationship between gap coverage and cold voltage. [Figure 6] FIG. 13 is a diagram showing the relationship between the gap coverage rate and the number density of cracks. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] An embodiment of the present invention will be described in detail below. [1. Gas diffusion layer] The gas diffusion layer according to the present invention is A porous substrate made of a conductive material; A microporous layer formed on the surface of the substrate; It is equipped with:
[0017] [1. Gas diffusion layer] [1.1. Base material] [1.1.1. Materials] In the present invention, the material of the substrate is not particularly limited, and an optimal material can be selected depending on the purpose. Examples of the substrate material include water-repellent carbon fiber nonwoven fabric, water-repellent carbon paper, and water-repellent carbon cloth.
[0018] 1.1.2. Thickness The thickness of the substrate is not particularly limited, and an optimal thickness can be selected according to the purpose. In general, if the thickness of the substrate is too thin, the spring property decreases, and assembly failure may occur when assembling the substrate to a fuel cell. In addition, if the thickness of the substrate is too thin, flooding may increase. This is because heat dissipation through the ribs is promoted, and the temperature of the substrate decreases. Therefore, the thickness of the substrate is preferably 70 μm or more. The thickness of the substrate is more preferably 80 μm or more, and more preferably 100 μm or more. On the other hand, if the thickness of the substrate is too thick, the gas diffusion resistance increases, and the output of the fuel cell may decrease. Therefore, the thickness of the substrate is preferably 300 μm or less. The thickness of the substrate is more preferably 250 μm or less, and further preferably 200 μm or less.
[0019] [1.1.3. Porosity] The porosity of the substrate in an uncompressed state is not particularly limited, and an optimal porosity can be selected depending on the purpose. Generally, if the porosity in the uncompressed state becomes too small, the temperature will drop due to heat radiation, which may cause flooding. Therefore, the porosity is preferably 65% or more. On the other hand, if the porosity in the uncompressed state is too large, the electrical conductivity of the substrate may be insufficient, so the porosity is preferably 85% or less.
[0020] [1.2. Microporous layer] [1.2.1. Materials] A microporous layer (hereinafter, also referred to as "MPL") is formed on the surface of the substrate on the catalyst layer side. The MPL is intended to promote the discharge of water generated in the catalyst layer. The material of the MPL is not particularly limited as long as it exhibits such a function. The MPL is generally made of a mixture of conductive particles made of a conductive material and a water-repellent resin. Examples of the conductive particles include carbon black, carbon fiber, graphite, activated carbon, etc. Examples of the water-repellent resin include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyhexafluoropropylene, etc.
[0021] [1.2.2. Number density of cracks] What is a "crack"? (a) The length (straight-line distance) from the start point to the end point is 80 μm or more, (b) The maximum width of the microporous layer on the surface is 20 μm or less, and (c) Penetrating the microporous layer This refers to a linear defect. "Crack density (pcs / mm 2 ) is the number of cracks per unit area, and the number of cracks N that appear in the observation area on the surface of the MPL is multiplied by the area S (≧27 mm 2 ) (=N / S).
[0022] The cracks in the MPL have the function of draining water generated in the catalyst layer to the substrate side. Therefore, if the crack density becomes too small, the drainage performance of the gas diffusion layer may decrease. Therefore, the crack density should be less than 2 / mm 2 The number density should be 3 / mm or more. 2 More preferably, 4 pieces / mm2 That's all. On the other hand, if the crack density becomes too high, the MPL may break during cell assembly. Therefore, the crack density should be less than 11 / mm 2 The number density should be less than 10 particles / mm 2 Less than 9 pieces / mm 2 The following is the result.
[0023] [1.2.3. Recess area ratio] The term "recess" refers to a region in which the average motif length measured in accordance with JIS B0671-2002 is 100 μm or more. "Area ratio of recessed portions" refers to the ratio of the area of recessed portions to the area of the surface of the MPL.
[0024] The area ratio of the recesses affects the amount of gaps formed at the interface between the catalyst layer and the MPL when a fuel cell is produced using the gas diffusion layer. The amount of gaps also affects the drainage performance of the gas diffusion layer. In general, if the area ratio of the recesses is too small, the amount of gaps formed at the catalyst layer / MPL interface becomes excessively small, and drainage performance may decrease. Therefore, the area ratio of the recesses needs to be 11% or more. The area ratio is preferably 12% or more, and more preferably 13% or more. On the other hand, if the area ratio of the recesses is too large, the amount of gaps formed at the catalyst layer / MPL interface becomes excessively large, and drainage performance may deteriorate. Therefore, the area ratio of the recesses must be 15% or less. The area ratio is preferably 14.5% or less, and more preferably 14% or less.
[0025] Thickness The thickness of the MPL affects the area ratio of the recesses. In general, if the thickness of the MPL is too thin compared to the unevenness of the substrate, the unevenness of the substrate will appear as it is on the surface of the MPL, and the area ratio of the recesses may become excessively large. Therefore, the thickness of the MPL is preferably 10 μm or more. The thickness is more preferably 15 μm or more, and more preferably 20 μm or more. On the other hand, the thicker the MPL, the flatter the surface of the MPL becomes. However, if the MPL becomes too thick, the gas diffusion resistance increases and the output of the fuel cell decreases. Therefore, the thickness of the MPL is preferably 60 μm or less. The thickness is more preferably 50 μm or less, and even more preferably 40 μm or less.
[0026] [1.3. Usage] The gas diffusion layer according to the present invention can be used as either a cathode side gas diffusion layer or an anode side gas diffusion layer. The gas diffusion layer according to the present invention is particularly suitable as a cathode side gas diffusion layer. Since flooding is likely to occur on the cathode side, using the gas diffusion layer according to the present invention as the cathode side gas diffusion layer can suppress flooding.
[0027] [2. Polymer electrolyte fuel cell] The polymer electrolyte fuel cell according to the present invention comprises: a membrane electrode assembly in which a cathode catalyst layer and an anode catalyst layer are bonded to both sides of an electrolyte membrane made of a solid polymer electrolyte membrane; a cathode-side gas diffusion layer disposed on the outer side of the cathode-side catalyst layer; an anode-side gas diffusion layer disposed on the outer side of the anode-side catalyst layer; a cathode-side separator disposed on the outer side of the cathode-side gas diffusion layer; an anode-side separator disposed on the outer side of the anode-side gas diffusion layer; It is equipped with:
[0028] [2.1. Membrane electrode assembly] The membrane electrode assembly (MEA) is composed of a cathode catalyst layer and an anode catalyst layer bonded to both sides of an electrolyte membrane made of a solid polymer electrolyte. The cathode catalyst layer and the anode catalyst layer each consist of a composite of an electrode catalyst and a catalyst layer ionomer. In the present invention, the type of solid polymer electrolyte constituting the electrolyte membrane is not particularly limited, and an optimum material can be selected depending on the purpose. Similarly, the types of the electrode catalyst and catalyst layer ionomer contained in the catalyst layer are not particularly limited, and the most suitable materials can be selected depending on the purpose.
[0029] [2.2. Cathode side gas diffusion layer] 2.2.1. Structure A cathode-side gas diffusion layer is disposed on the outer side of the cathode-side catalyst layer of the MEA. In the present invention, the gas diffusion layer according to the present invention is used as the cathode-side gas diffusion layer. Details of the gas diffusion layer are as described above, and therefore will not be described here.
[0030] [2.2.2. Gap coverage] "Gap" refers to a planar defect that exists at the interface between the cathode-side catalyst layer and the microporous layer of the cathode-side gas diffusion layer, The "coverage rate of the gaps" refers to the ratio of the area of the gaps to the surface area of the microporous layer.
[0031] A polymer electrolyte fuel cell is obtained by stacking the MEA, gas diffusion layer, and separator and clamping them under a certain clamping pressure. At this time, by optimizing the structure of the gas diffusion layer and the separator, as well as the clamping pressure, an appropriate gap can be formed between the cathode catalyst layer and the MPL. The gap formed between the cathode catalyst layer and the MPL affects the drainage performance of the cathode gas diffusion layer.
[0032] If the coverage of the gap is too small, the contact area between the cathode catalyst and the MPL increases, which promotes heat dissipation from the cathode catalyst, and may result in a decrease in the drainage performance of the cathode-side gas diffusion layer. Therefore, the coverage of the gap is preferably 11% or more. The coverage is more preferably 12% or more, and even more preferably 13% or more. On the other hand, if the gap coverage is too high, the insulation of the interface is improved more than necessary, and flooding may occur in the MPL. Therefore, the gap coverage is preferably 15% or less. The gap coverage is more preferably 14.5% or less, and even more preferably 14% or less.
[0033] [2.3. Anode side gas diffusion layer] An anode-side gas diffusion layer is disposed on the outer side of the anode-side catalyst layer of the MEA. In the present invention, the structure of the anode-side gas diffusion layer is not particularly limited. The anode-side gas diffusion layer usually comprises a porous substrate made of a conductive material and a microporous layer formed on the surface of the substrate. The anode-side gas diffusion layer may have the same structure as the cathode-side gas diffusion layer, or may have a different structure. Other points regarding the anode-side gas diffusion layer are the same as those of the cathode-side gas diffusion layer, so a description thereof will be omitted.
[0034] [2.4. Cathode side separator] A cathode-side separator is further disposed on the outer side of the cathode-side gas diffusion layer. The cathode-side separator has a gas flow path for flowing an oxidant gas. In the present invention, the structure of the cathode-side gas diffusion layer is not particularly limited as long as it is capable of supplying an oxidant gas to the cathode-side catalyst layer.
[0035] The cathode separator is preferably one having a structure in which a plurality of linear gas flow paths are arranged in parallel with ribs interposed therebetween. In this case, the width and pitch of the ribs affect the performance of the polymer electrolyte fuel cell.
[0036] If the rib width is too narrow, the carbon fiber of the base material may break. Therefore, the rib width is preferably 0.1 mm or more. The rib width is more preferably 0.2 mm or more, and even more preferably 0.5 mm or more. On the other hand, if the rib width is too wide, the gas diffusion resistance under the rib may increase. Therefore, the rib width is preferably 2.0 mm or less. The rib width is more preferably 1.5 mm or less, and even more preferably 1.0 mm or less.
[0037] If the rib pitch is too narrow, pressure loss may increase. Therefore, the rib pitch is preferably 0.3 mm or more. The rib pitch is more preferably 0.5 mm or more, and even more preferably 1.0 mm or more. On the other hand, if the rib pitch is too wide, the effective cross-sectional area of the flow path is reduced due to bending of the substrate, which may increase pressure loss. Therefore, the rib pitch is preferably 2.0 mm or less. The rib pitch is more preferably 1.5 mm or less, and even more preferably 1.0 mm or less.
[0038] [2.5. Anode side separator] An anode-side separator is further disposed on the outer side of the anode-side gas diffusion layer. The anode-side separator has a gas flow path for allowing a fuel gas to flow. In the present invention, the structure of the anode-side gas diffusion layer is not particularly limited as long as it is capable of supplying the fuel gas to the anode-side catalyst layer. The anode-side separator may have the same structure as the cathode-side separator, or may have a different structure. Other points regarding the anode-side separator are the same as those of the cathode-side separator, so the description will be omitted.
[0039] [2.6. Clamping pressure] The clamping pressure when producing a polymer electrolyte fuel cell affects the gap coverage. In general, if the clamping pressure is too low, the gap coverage may become excessively high. Therefore, the clamping pressure is preferably 0.8 MPa or more. The clamping pressure is more preferably 0.9 MPa or more, and even more preferably 1.0 MPa or more. On the other hand, if the clamping pressure is too high, the coverage of the gap may become excessively small. Therefore, the clamping pressure is preferably 2.0 MPa or less. The clamping pressure is more preferably 1.8 MPa or less, and even more preferably 1.6 MPa or less.
[0040] 2.7. Cold voltage "Cold voltage" refers to the voltage at which the cell temperature is started at 30°C and the current density is 1A / cm2 after 10 seconds. 2 This refers to the cell voltage when
[0041] When a fuel cell is started at a low temperature, the generated water is likely to condense at the cathode. In this case, if the drainage performance of the cathode-side gas diffusion layer is poor, the generated water is likely to accumulate in the cathode-side gas diffusion layer. If the generated water accumulates in the cathode-side gas diffusion layer, oxygen diffusion is hindered, and the cell voltage decreases. In contrast, the fuel cell according to the present invention has high drainage performance because the crack density and gap coverage of the MPL are optimized, and therefore the cold voltage is 0.65 V or higher. By further optimizing the manufacturing conditions of the fuel cell, the cold voltage can be 0.655 V or higher, or 0.66 V or higher.
[0042] [3. Manufacturing method of gas diffusion layer] The method for producing a gas diffusion layer according to the present invention comprises the steps of: A first step of preparing a porous substrate made of a conductive material; a second step of mixing the conductive particles, the water-repellent resin, the dispersant, the thickener, and water to prepare a slurry; A third step of applying the slurry to a surface of the substrate and drying the slurry; A fourth step of calcining the substrate to obtain the gas diffusion layer according to the present invention. It is equipped with:
[0043] [3.1. 1st step] First, a porous substrate made of a conductive material is prepared (first step). In the present invention, the type of the substrate is not particularly limited. A commercially available substrate may be used as is, or a commercially available substrate may be subjected to necessary treatment.
[0044] For example, in the case of a carbon fiber nonwoven fabric, the carbon fibers are merely physically entangled, and the fibers tend to fall apart if left as is. When using such a material as the base material of a gas diffusion layer, it is preferable to bond the fibers together using a resin that can be carbonized. The type of resin is not particularly limited as long as it can be carbonized, and examples of the resin include phenol resin and acrylic resin.
[0045] Specifically, the treatment of the porous substrate with the phenolic resin is preferably carried out as follows. That is, after impregnating a porous substrate (e.g., carbon fiber nonwoven fabric) with a phenolic resin solution, the excess resin solution is blown off with compressed air, leaving the resin solution only in areas with a small radius of curvature inside the substrate (e.g., areas near the contact points between fibers). The substrate is then dried and then fired in a reducing atmosphere to carbonize the resin, thereby reinforcing the substrate while maintaining its porosity. The baking temperature is preferably selected optimally depending on the type of resin. For example, in the case of a phenolic resin, the baking temperature is preferably 500°C to 1000°C.
[0046] [3.2. 2nd process] Next, the conductive particles, the water-repellent resin, the dispersant, the thickener, and water are mixed together to prepare a slurry (second step). The conductive particles and the water-repellent resin are the raw materials of MPL. Details of the conductive particles and the water-repellent resin are as described above, and therefore will not be described here. The dispersant is for dispersing the conductive particles and the water-repellent resin in water. The thickener is for increasing the viscosity of the slurry. In the present invention, the materials of the dispersant and the thickener are not particularly limited, and the most suitable material can be selected depending on the purpose.
[0047] The solids concentration and viscosity of the slurry affect the number density of cracks and the area ratio of recesses in the MPL, as well as the coverage of gaps when a fuel cell is fabricated using the gas diffusion layer. Therefore, it is preferable to select these so as to obtain the desired structure. In general, the higher the solid content of the slurry, the higher the number density of cracks. Also, the higher the solid content of the slurry, the less the slurry penetrates into the substrate, so the area ratio of the recesses and / or the coverage of the gaps tend to be smaller. Specifically, the solid content is preferably 70% by weight to 90% by weight.
[0048] In general, the higher the viscosity of the slurry, the slower the water transfer rate in the coating film during drying, and therefore the number density of cracks tends to be higher. Also, the higher the viscosity of the slurry, the less the slurry penetrates into the substrate, and therefore the area ratio of the recesses and / or the coverage rate of the gaps tends to be smaller. Specifically, the viscosity of the slurry is 1×10 3 mPa s~1×10 5 mPa·s is preferred.
[0049] [3.3. Third step] Next, the slurry is applied to the surface of the substrate and dried (third step). The amount of slurry applied, the pressure at which the slurry is applied, and the drying conditions affect the number density of cracks in the MPL, the area ratio of recesses, and the coverage of gaps, so it is preferable to select these factors so as to obtain the desired structure.
[0050] In general, the more the amount of slurry applied, the higher the number density of cracks tends to be. Also, the more the amount of slurry applied, the lower the area ratio of recesses and / or the coverage rate of gaps tends to be. Furthermore, the more the amount of slurry applied, the thicker the MPL obtained by drying the slurry becomes. Therefore, it is preferable to select the optimal amount of slurry applied, taking these factors into consideration.
[0051] In general, the faster the drying speed of the coating film, the higher the number density of cracks tends to be. Also, the faster the drying speed of the coating film, the more water-repellent resin gathers on the substrate surface, so the area ratio of recesses and / or the coverage rate of gaps tends to be smaller. The drying speed (amount of solvent evaporated per unit area and unit time) is specifically 2.0 g / m 2 s~200g / m 2 ·s is preferred.
[0052] [3.4. 4th step] Next, the substrate is fired (fourth step), thereby obtaining the gas diffusion layer according to the present invention. The baking is performed to melt the water-repellent resin contained in the coating film and bond the substrate and MPL via the water-repellent resin. The baking temperature is preferably selected to be optimal depending on the type of water-repellent resin. For example, when the water-repellent resin is PTFE, the baking temperature is preferably 250°C to 290°C.
[0053] [4. Effect] When a microporous layer is formed on the surface of a porous substrate, optimizing the manufacturing conditions makes it possible to obtain a gas diffusion layer in which the number density of cracks and the area ratio of recesses are within a predetermined range. Next, in the case of producing a polymer electrolyte fuel cell using such a gas diffusion layer, by optimizing the production conditions, it is possible to form appropriate voids at the interface between the cathode side catalyst layer and the microporous layer. Both the cracks in the microporous layer and the gaps at the cathode catalyst layer / microporous layer interface affect the drainage performance on the cathode side. Therefore, optimizing the manufacturing conditions to optimize these factors leads to a polymer electrolyte fuel cell that exhibits a high cold voltage. EXAMPLES
[0054] (Examples 1 to 2, Comparative Examples 1 to 5) [1. Sample preparation] [1.1. Preparation of gas diffusion layer] After impregnating the carbon fiber nonwoven fabric with phenolic resin, the excess phenolic resin was blown off with compressed air. The nonwoven fabric was blown at a specified speed (1 g / m 2 s~500g / m 2 After drying at 100°C (s), it was fired in a reducing atmosphere to carbonize the phenolic resin contained in the nonwoven fabric. Next, carbon particles, PTFE particles, polyethylene oxide (thickener), and a dispersant are added to water to obtain a mixture with a predetermined viscosity (9×10 2 mPa s~5×10 7 A slurry with a viscosity of 100 mPa s was prepared. The slurry was applied to a nonwoven fabric, which was then dried (100°C) and sintered (290°C) at a specified temperature to obtain a gas diffusion layer (GDL) with a microporous layer (MPL).
[0055] [1.2. Preparation of fuel cell] A gas diffusion layer and a separator were placed on both sides of the MEA to obtain a fuel cell. The cathode side gas diffusion layer and the anode side gas diffusion layer were prepared as described in [1.1.]. The anode side separator and the cathode side separator were each equipped with a structure in which multiple linear gas channels were arranged in parallel with ribs interposed therebetween. The rib width was 1.0 mm, and the rib pitch was 1.0 mm. The cathode side gas channel and the anode side gas channel were arranged so that the flow directions were opposite each other.
[0056] 2. Test Method [2.1. Recess area ratio] The average motif length of the MPL surface was measured based on the roughness curve obtained using a laser microscope in accordance with JIS B0671-2002. Furthermore, the area ratio of the recesses with an average motif length of 100 μm or more was calculated.
[0057] [2.2. X-ray CT] [2.2.1. Measurement method] A schematic diagram of an X-ray CT measurement jig is shown in Fig. 1. In Fig. 1, an X-ray CT measurement jig 10 includes a lower bar 12 made of stainless steel and an upper bar 14 made of stainless steel. The sample 20 was inserted between the lower rod 12 and the upper rod 14. The sample 20 was, from the bottom, (a) A jig 22 simulating a flow path structure; (b) A gas diffusion layer (GDL) 24 having an MPL 24b formed on the surface of a substrate 24a; (c) a catalytic coating layer (CCM) 26; and (d) 500 μm thick polytetrafluoroethylene (PTFE) sheet 28 The above-mentioned components are stacked one on top of the other.
[0058] The jig 22 is composed of three rods 22b simulating ribs arranged in parallel on the upper surface of a disk 22a. The GDL 24 is placed on the jig 22 with the MPL 24b facing up. The CCM 26 simulates an MEA and has the same structure as an MEA except that it does not contain catalyst particles (Pt particles). After setting the sample 20 between the lower rod 12 and the upper rod 14, the sample 20 was pressurized using a load cell. The pressure was set to 1.1 MPa. In this state, an X-ray CT image of the MPL / CCM interface was taken using an X-ray CT device. Furthermore, an in-plane cross-sectional image was extracted from the X-ray CT image.
[0059] [2.2.2. Measurement of gap coverage and crack density] Figure 2(A) shows an example of an X-ray CT image of a longitudinal section of a laminate of a gas diffusion layer (GDL) and a catalyst coated membrane (CCM). Figure 2(B) shows an in-plane cross-sectional image (including gaps) of the microporous layer (MPL) / catalyst layer (CL) interface extracted from the X-ray CT image. Figure 2(C) shows an in-plane cross-sectional image (including cracks) of the microporous layer (MPL) / catalyst layer (CL) interface extracted from the X-ray CT image. Figure 2 shows that the gaps and cracks at the MPL / CL interface can be easily confirmed from the in-plane cross-sectional image of the interface.
[0060] Figure 3(A) shows an example of an in-plane cross-sectional image of the microporous layer (MPL) / catalyst layer (CL) interface extracted from an X-ray CT image. Figure 3(B) shows a schematic diagram of a gap contained in the in-plane cross-sectional image. Figure 3(C) shows a schematic diagram of a crack contained in the in-plane cross-sectional image. The in-plane cross-sectional image in Fig. 3(A) was binarized to obtain the binarized image shown in Fig. 3(B). The obtained binarized image was used to calculate the coverage of the gap. In addition, cracks were manually extracted from the in-plane cross-sectional image in Figure 3(A) to obtain the image shown in Figure 3(C). The number density of cracks was calculated by dividing the number of cracks in the image by the area of the image.
[0061] [2.3. Cold voltage] The cold voltage of the resulting fuel cell was measured under the condition of constant voltage acceleration from 30°C.
[0062] [3. Results] The results are shown in Table 1. Figure 4 shows the relationship between the crack number density and cold voltage. Figure 5 shows the relationship between the gap coverage rate and cold voltage. Furthermore, Figure 6 shows the relationship between the gap coverage rate and the crack number density. The following can be seen from Table 1 and Figures 4 to 6.
[0063] (1) A correlation was observed between the crack density and the cold voltage (Fig. 4). 2 When the crack density was less than 11 / mm, the cold voltage sometimes decreased. This is thought to be due to the decrease in drainage. 2 When the temperature exceeded 100°C, the cold voltage sometimes decreased. This is thought to be due to some of the MPLs being broken. (2) A correlation was observed between the gap coverage and the cold voltage (Figure 5). When the gap coverage was less than 11%, the cold voltage sometimes decreased. This is believed to be due to flooding in the catalyst layer. On the other hand, when the gap coverage was more than 15%, the cold voltage sometimes decreased. This is believed to be due to flooding in the MPL.
[0064] (3) In both Example 1 and Example 2, a cold voltage of 0.65 V or more was achieved. From FIG. 6, in order to achieve a cold voltage of 0.65 V or more, the number density of cracks needs to be 2 / mm 2 More than 11 pieces / mm 2 It was found that the gap coverage rate must be between 11% and 15%. (4) When the number density of cracks on the MPL surface was compared before and after compressing the GDL, it was found that there was no change in the number density of cracks before and after compression. In other words, it was found that the number density of cracks is almost determined by the manufacturing conditions of the GDL.
[0065] [Table 1]
[0066] Although the embodiment of the present invention has been described in detail above, the present invention is not limited to the above embodiment, and various modifications are possible without departing from the gist of the present invention. [Industrial Applicability]
[0067] The gas diffusion layer according to the present invention can be used in solid polymer fuel cells, polymer electrolyte membrane water electrolysis devices, and the like.
Claims
1. A porous substrate made of a conductive material; A microporous layer formed on the surface of the substrate; Equipped with The microporous layer is The crack density is 2 / mm 2 More than 11 pieces / mm 2 is as follows: The area ratio of the recesses is 11% or more and 15% or less. Gas diffusion layer. Where: "Crack" refers to a linear defect having a length (straight-line distance) from the start point to the end point of 80 μm or more, a maximum width appearing on the surface of the microporous layer of 20 μm or less, and penetrating the microporous layer; "Recess" refers to a region in which the motif average length measured in accordance with JIS B0671-2002 is 100 μm or more; The "area ratio of the recesses" refers to the ratio of the area of the recesses to the surface area of the microporous layer.
2. 2. The gas diffusion layer according to claim 1, wherein the substrate has a thickness of 70 μm or more and 300 μm or less, and a porosity in an uncompressed state of 65% or more and 85% or less.
3. The gas diffusion layer according to claim 1 or 2, wherein the microporous layer has a thickness of 10 μm or more and 60 μm or less.
4. The gas diffusion layer according to claim 1 , which is used as a cathode side gas diffusion layer.
5. A polymer electrolyte fuel cell having the following configuration. (1) The solid polymer electrolyte fuel cell is a membrane electrode assembly in which a cathode catalyst layer and an anode catalyst layer are bonded to both sides of an electrolyte membrane made of a solid polymer electrolyte membrane; a cathode-side gas diffusion layer disposed on the outer side of the cathode-side catalyst layer; an anode-side gas diffusion layer disposed on the outer side of the anode-side catalyst layer; a cathode-side separator disposed on the outer side of the cathode-side gas diffusion layer; an anode-side separator disposed on the outer side of the anode-side gas diffusion layer; It is equipped with: (2) The cathode side gas diffusion layer is formed of the gas diffusion layer according to any one of claims 1 to 3.
6. 6. The polymer electrolyte fuel cell according to claim 5, wherein the gap coverage is 11% or more and 15% or less. Where: "Gap" refers to a planar defect that exists at the interface between the cathode-side catalyst layer and the microporous layer of the cathode-side gas diffusion layer, The "coverage rate of the gaps" refers to the ratio of the area of the gaps to the surface area of the microporous layer.
7. the cathode-side separator has a structure in which a plurality of linear gas flow paths are arranged in parallel with ribs interposed therebetween, The width of the rib is 0.1 mm or more and 2.0 mm or less, The pitch of the ribs is 0.3 mm or more and 2.0 mm or less. The polymer electrolyte fuel cell according to claim 5 or 6.
8. 8. The polymer electrolyte fuel cell according to claim 5, wherein the clamping pressure is 0.8 MPa or more and 2.0 MPa or less.
9. 9. The polymer electrolyte fuel cell according to claim 5, wherein the cold voltage is 0.65 V or more. Here, the "cold voltage" refers to the voltage at which the cell temperature is started at 30°C and the current density is 1 A / cm2 after 10 seconds. 2 This refers to the cell voltage when
10. A first step of preparing a porous substrate made of a conductive material; a second step of mixing the conductive particles, the water-repellent resin, the dispersant, the thickener, and water to prepare a slurry; A third step of applying the slurry to a surface of the substrate and drying the slurry; A fourth step of calcining the substrate to obtain the gas diffusion layer according to any one of claims 1 to 4. A method for manufacturing a gas diffusion layer comprising the steps of:
Citation Information
Patent Citations
Electrode for fuel cell and its manufacture
JP2000228204A
Polymer electrolyte type fuel cell, and manufacturing method of its electrode
JP2004164903A
Electrode for fuel cell, fuel cell, and manufacturing method therefor
JP2006019300A
Accelerating drainage of fuel cell
JP2008034301A
Film assembly for electrode of fuel cell and fuel cell
JP2008277126A